2019
DOI: 10.3892/etm.2019.7516
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric virology and human papillomaviruses: An update

Abstract: Almost 10 years ago, in October, 2008, the scientist who reported for the first time the association between human papillomaviruses (HPV) and cervical cancer, was awarded with the Nobel prize. In the years that followed, Professor Harald zur Hausen actively supported the value of the HPV vaccination in the prevention of different types of cancer and highlighted the necessity of its introduction in both girls and boys. However, to date, in the majority of countries, HPV vaccination among male adolescents has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…These ingredients are additional foreign agents that overwhelm the immune system (see below). The ingredients that are perceived as 'natural' [eg, fetal serum, clumps of tissue/organ or DNA particles, proteins-peptides (eg, ovalbumin, egg † † † † † † † † Government Corruption AUGUST 20, 2020 1,4,5,8,12,14,17,[31][32][33][34][35][36][37][38][39][40]50,58,[61][62][63][64][66][67][68]70,71,141,144,148,152,153,156,165,167,168 (Figures 3-5).…”
Section: Vaccines Incipient (Ingredient Adjuvant Excipient): Mini Ementioning
confidence: 99%
“…These ingredients are additional foreign agents that overwhelm the immune system (see below). The ingredients that are perceived as 'natural' [eg, fetal serum, clumps of tissue/organ or DNA particles, proteins-peptides (eg, ovalbumin, egg † † † † † † † † Government Corruption AUGUST 20, 2020 1,4,5,8,12,14,17,[31][32][33][34][35][36][37][38][39][40]50,58,[61][62][63][64][66][67][68]70,71,141,144,148,152,153,156,165,167,168 (Figures 3-5).…”
Section: Vaccines Incipient (Ingredient Adjuvant Excipient): Mini Ementioning
confidence: 99%
“…Self-inoculation is described in studies as a potential HPV transmission route. It has been detailed in studies of HPV in female virgins (16), in children with genital warts (low-risk HPV) without a history of sexual abuse (17). A study on female virgins found 51.1% HPV positive, compared with 69.1% of sexually active females.…”
Section: Routes For Hpv Transmissionmentioning
confidence: 99%
“…To date, he has been a great benefactor of the Paediatric Virology Study Group (PVSG) since its birth (22). He has hosted all ‘workshops on Paediatric Virology’ organized by PVSG (2328) and he has co-authored the 2015 proposal of Paediatric Virology subspecialty (29). In 2017, the participation in the ‘3rd workshop on Paediatric Virology’ of two top worldwide experts in Paediatric Virology, Nobelist Laurate Professor of Virology Harald zur Hausen (Germany) and Professor of Neonatology Anne Greenough (UK), was the proof of the high-level scientific standards guaranteed by Professor Spandidos (25) and his fundamental contribution to medical education (30).…”
Section: Introductionmentioning
confidence: 99%